Ethics of Political Communication in the Media Space of Time in the Digital Era - Erwan Efendi; Abdul Rasyid (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The rapid development of digital media has transformed political communication practices by enabling faster information dissemination, broader public participation, and greater interaction between political actors and audiences. However, these developments have also raised ethical concerns regarding the accuracy, objectivity, and responsibility of political communication in digital environments. Despite extensive discussions on digital political communication, limited research has specifically examined how political communication ethics are practiced within digital mass media and how these practices influence the quality of political information and public opinion formation. This study aims to analyze the implementation of political communication ethics in digital media, identify the factors influencing its application, and examine its implications for political information quality and public opinion formation. A qualitative approach with a descriptive-interpretive method was employed. The research participants consisted of online journalists, editors, and media and political communication experts selected through purposive sampling. Data were collected through non-participant observation of political news content, in-depth semi-structured interviews, and documentary analysis of news texts, journalistic codes of ethics, and editorial policies. Data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that the implementation of political communication ethics in digital media is often situational and characterized by compromises between ethical standards, market demands, and political interests. Individual factors, organizational structures, and socio-cultural dynamics within the media ecosystem influence the practice. Furthermore, inconsistencies in ethical implementation contribute to the decline of political information quality and encourage the emergence of emotional, polarized, and less rational public opinion. The study concludes that strengthening political communication ethics is essential for maintaining information credibility and promoting democratic discourse in the digital era. This research contributes to the development of political communication theory by highlighting the interaction between ethical principles and digital media dynamics, while also providing practical recommendations for media organizations, journalists, and policymakers to enhance ethical standards in political communication.